2016
DOI: 10.15628/holos.2016.2782
|View full text |Cite
|
Sign up to set email alerts
|

Contaminação Microbiológica No Perfil Do Solo Por Águas Residuárias.

Abstract: Presente trabalho teve como objetivo analisar a população de coliformes totais, termotolerantes e a Salmonella presentes no solo irrigado com efluente doméstico tratado. As amostras do solo foram coletadas com trado holandês, nos meses de abril e setembro de 2012 no período chuvoso e seco respectivamente, na área do cultivo do capim-elefante (P. purpureum) irrigada com água residuária de origem domestica. as amostras foi feita em 12 pontos aleatórios, nas linhas do plantio com profundidades de 0 - 0,40 m, em o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
(3 reference statements)
0
4
0
3
Order By: Relevance
“…However, the risk can be reduced through good practices, using personal protective equipment (PPE) in agriculture (WHO, 2006), so it is essential to know the contaminants and pollutants that may be in the reuse water. In addition, the transmission of diseases becomes less or even controlled through irrigation, culture and harvesting practices used, for example, application of drip irrigation (Morais et al, 2016;Mancuso and Santos, 2013;WHO, 2006). Gatta et al (2016) found that despite identifying microorganisms such as E. coli and Salmonella spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the risk can be reduced through good practices, using personal protective equipment (PPE) in agriculture (WHO, 2006), so it is essential to know the contaminants and pollutants that may be in the reuse water. In addition, the transmission of diseases becomes less or even controlled through irrigation, culture and harvesting practices used, for example, application of drip irrigation (Morais et al, 2016;Mancuso and Santos, 2013;WHO, 2006). Gatta et al (2016) found that despite identifying microorganisms such as E. coli and Salmonella spp.…”
Section: Resultsmentioning
confidence: 99%
“…There are currently several examples of reusing water in agriculture in Brazil and worldwide (Fito and Van Hulle, 2021;Mancuso and Santos, 2013). Reused water is defined as the reuse of water from treated effluents (Morais et al, 2016). It can be classified according to Moura et al (2020), who conceptualized the origin of reuse water as follows:…”
Section: Introductionmentioning
confidence: 99%
“…O risco maior existe do contato da água de reúso com a parte externa, de permanecer resíduos contaminantes e poluentes sobre as folhas e caules. A transmissão de doenças se torna menor ou mesmo controlada por meio de práticas de irrigação, de cultura e de colheita utilizadas, por exemplo, aplicação de irrigação por gotejamento e uso de equipamentos de proteção individual pelos agricultores (MORAIS et al, 2016;MANCUSO;SANTOS, 2013;WHO, 2006). Além disso, a utilização da água de reúso pode representar uma fonte de nutrientes disponíveis para aplicação na agricultura MANCUSO;SANTOS, 2013).…”
Section: Resultsunclassified
“…No Brasil e no mundo, existem vários exemplos da utilização de água de reúso na agricultura (MANCUSO;SANTOS, 2013). A água de reúso é definida como a reutilização de águas provenientes de efluentes tratados (MORAIS et al, 2016). A agricultura é a atividade econômica que mais demanda água, cerca de 70% (WHO, 2013), e devido à escassez das fontes hídricas para esta atividade em diversas regiões, a água de reúso se torna uma alternativa para enfrentamento desse problema .…”
Section: Introductionunclassified
“…2 Reused water is defined as the reuse of water, which comes from treated effluents. 9 The reused water can be classified according to Moura et al Considering that, according to GONÇALVES (2009), black waters are effluents from toilets, basically containing feces, urine and toilet paper or from feces and urine separating devices, having in their composition large amounts of fecal matter and toilet paper; suspended solids, largely sedimentable; (iii) Industrial reuse, coming from water from the industrial activities of the enterprise itself (direct internal reuse) or from external reuse. "…”
Section: Introductionmentioning
confidence: 99%